If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(x-2)+2=6x+2(-5+x)
We simplify the equation to the form, which is simple to understand
8(x-2)+2=6x+2(-5+x)
Reorder the terms in parentheses
+(+8x-16)+2=6x+2*(-5+x)
Remove unnecessary parentheses
+8x-16+2=+6x+2+*(-5+x+)
Reorder the terms in parentheses
+8x-16+2=6x+(-10+2x)
Remove unnecessary parentheses
+8x-16+2=+6x-10+2x
We move all terms containing x to the left and all other terms to the right.
+8x-6x-2x=-10+16-2
We simplify left and right side of the equation.
0x=+4
0=4
The left and right sides are not equal, therefore there is no solution. This equation is invalid.
| 7*a-2*5-2*6*a+5= | | x^2+7x+10=(x+5)(x+2) | | 5y-7=2y+11 | | 4+8+4+2=4396 | | 4+3+9+6=5482 | | .40x+.90(600)=.60(800+x) | | x^4+2x^3+3x^2+x+2=0 | | 6(2x-7)+6=12x-36 | | 39-5x=13x+19 | | -a^2+20a-60=0 | | 25x^2+10x+1=7 | | 16x^2-8x+1=11 | | x=4y*1.2 | | x^2-6x+9=9 | | 34=10+4q | | 5s^2+23s+24=0 | | -2X^2+14X+196=0 | | a+a=a | | 2q+2=-12 | | 4x^2+28X=240 | | 2x-4=x+9 | | (x-2)(3x+8)=0 | | ln(x)+ln(x-6)=ln(16) | | (50-4y)+(25-2x)=100 | | -36+2w=8w+w | | 7X-8X-9X+2+3+17X=12 | | 111111111111111111111(a)= | | -x-4=16 | | -10=6+2c | | 5.25+x=3.75 | | b+5=-13 | | x-(x*0.2)=9.6 |